PENGARUH SENAM ERGONOMIK TERHADAP KELUHAN NYERI SENDI PADA LANSIA DI PSTW SABAI NAN ALUIH SICINCIN KABUPATEN PADANG PARIAMAN - Sari, Yade Kurnia; Esti, Amira; Adha, Salsabilla Adila (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Joint pain is a common disease in the elderly, one of the non-pharmacological therapies that can be done to reduce pain and muscle relaxation is ergonomic exercise. The purpose of this study was to reduce pain and as a phase of muscle relaxation. This study aims to determine the effect of ergonomic gymnastics on complaints of joint pain in the elderly at theTresna Werdha Sabai Nan Aluih Siring Social Institution in 2023. This study uses a pre-experimental design with a one-group pre-post test design, the study has been carried out in July-August 2023. With a total sample of 16 elderly results of the study obtained. joint pain in the elderly before ergonomic exercise had an average of 4.19 with moderate pain category. Joint pain in the elderly after ergonomic exercise has an average of 3.15 with a mild pain category. Ergonomic gymnastics has an effect on reducing the level of joint pain in the elderly obtained a value of p = 0.001 (α < 0.05).Keywords : ergonomicGymnastics, Paint Artrithis, erderly.